Cryogenic Deflashing for Rubber Products - Abhilash M.; Naveen Prakash G. V.; Kasthurirengan S. (MATEC Web of Conferences, 2018)
Deflashing is the process of removal of excess flashes from the rubber products. Initially deflashing was a manual operation where dozen of workers, seated at small work stations would take each part and trim the excess rubber off with scissors, knives or by grinding. Still the same method is employed in most of the rubber industry. The drawbacks of this method are demand inconsistent and repeatable quality. Work done by hand is often inconsistent. There are commercially available cryogenic deflashing machine but they are too expensive hence cost effectiveness is also a prime factor. The objective of this paper is to develop a technique, to identify the media through which the flashes can be removed easily and effectively. Based on the test results obtained from testing of five different types of media, ABCUT Steel media gave best results. The testing of the ABCUT Steel media on rubber samples like O-rings, grommet tail door, bottom bush etc. shows good results.